The Fourth Enemy : Journalism and Power in the Making of Peronist Argentina, 1930-1955 - Cane, James, 1968- (Book collections on Project MUSE., 2012)
"An interdisciplinary study examining the newspaper industry in Argentina during the regime of Juan Domingo Perón. Traces how Perón managed to integrate almost the entire Argentine press into a state-dominated media empire"--Provided by publisher.